Upper Airway Manifestations and Otolaryngologic Management of Bronchopulmonary Dysplasia in Preterm Infants: A Systematic Review - Almutairi, Mohammed; Alomari, Sahar; Alomari, Nujood; Aldhafeeri, Fahdah; Almutairi, Abeer; Alqathanin, Wajan; Aljifri, Hind; Alsaggaf, Sarah; Halawany, Khaled; Alhunaiti, Dana; Al-Qahtani, Hadeel; Felemban, Alla; et al. (ENT Updates, 2025)
Bronchopulmonary dysplasia (BPD) is a complex chronic lung disorder that affects extremely premature infants, particularly those born before 30 weeks of gestation or weighing less than 1500 g at birth. This systematic review aimed to evaluate the effectiveness of pharmacological interventions for BPD and to explore otolaryngologic manifestations and management strategies. A comprehensive literature search was conducted in the PubMed, Scopus, and Web of Science databases, yielding five studies that met the inclusion criteria. The studies investigated the effects of corticosteroids (prednisolone, hydrocortisone, and dexamethasone), erythropoietin, and diuretics on BPD outcomes. Prednisolone showed minimal short-term benefits, whereas hydrocortisone did not significantly reduce the incidence of BPD. However, extended dexamethasone regimens have been shown to improve survival rates without increasing complications. Early erythropoietin treatment reduced the incidence of BPD but did not affect hospital readmission rates. Diuretic use varied widely across centers, without clear survival or discharge benefits. Preterm infants with severe BPD requiring prolonged mechanical ventilation are at a high risk of subglottic stenosis, tracheomalacia, and vocal cord paralysis. Early diagnosis through airway endoscopy and multidisciplinary management, including tracheostomy for severe cases, are crucial for optimizing outcomes. BPD survivors may experience long-term respiratory impairment, exercise intolerance, and developmental delays, necessitating close monitoring and intervention. Future research should focus on developing standardized, evidence-based management protocols and exploring novel therapies to improve long-term respiratory and neurodevelopmental outcomes in this vulnerable population group.